Nanotechnology in solar energy: From active systems to Advanced Solar cells - Farajollahi, Amirhamzeh (Frontiers in Energy Research, 2025)
Nanotechnology has arisen as a revolutionary technology, providing a diverse range of solutions to tackle energy-related difficulties. Nanotechnology allows for the creation of components and devices that are smaller than 100 nm, which in turn provides new opportunities for improving the efficiency of energy capture, storage, and transport. Through the process of nuclear fusion, the sun produces a vast quantity of energy on a daily basis, surpassing all the energy that humanity has ever harnessed throughout history. The worldwide technical capacity of solar energy significantly surpasses the current overall primary energy requirement. This review explores the role of nanomaterials in improving solar energy harvesting systems, including solar collectors, fuel cells, photocatalytic systems, and photovoltaic cells. Through a systematic review of peer-reviewed studies, key findings indicate that nanomaterials can enhance incident solar radiation absorption by up to nine times, leading to a 10% efficiency improvement in solar collectors compared to conventional designs. Additionally, advancements in third-generation solar cells demonstrate the potential of nanostructured materials in enhancing charge transport, light absorption, and cost-effectiveness. The study further highlights existing challenges, such as the long-term stability of nanomaterials, environmental concerns, and economic barriers to large-scale implementation. Addressing these limitations through sustainable nanomaterial design and scalable production techniques will be essential for realizing the full potential of nanotechnology in solar energy applications.